A facile route to water-soluble coronenes and benzo[ghi]perylenes - Schmidt, Cordula; Lang, Nina; Jux, Norbert; Hirsch, Andreas (Chemistry - A European Journal, 2011)
Click reactions at the bay-position of perylenes and a new route to benzo[ghi]perylenes and coronenes are presented. Irradiation with light leads to an electrocyclic reaction of the newly formed triazole ring(s) with the neighbouring bay-positions of the perylene core and after oxidation by air, the benzo[ghi]perylenes and coronenes are obtained. By using Newkome dendrimers as substituents for perylene diimides (PDIs), water solubility can be achieved after removal of the tert-butyl protecting groups. The aggregation and optical properties of the bay-functionalised PDIs, benzo[ghi]perylenes and coronenes are investigated by absorption and fluorescence spectroscopy. Given the green light: Click reactions at the bay-positions of perylene diimides were carried out for the first time. The newly formed triazole units undergo electrocyclisation reactions with the neighbouring perylene bay-position to form benzoperylenes or coronenes (see scheme). The reactions occur in solution in 55-87%yield by irradiation with light, providing a simple, new and environmentally friendly route to coronenes and benzoperylenes. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.